A systematic review of the efficacy of traditional Chinese medicine retention enema in the treatment of ulcerative colitis - Jiaji Li; Ling Tang; Ye Li; Jingjin Xu; Jing Zhang (Wolters Kluwer Medknow Publications, 2024)
The objective of this study is to summarize the efficacy and safety of traditional Chinese medicine (TCM) enema in the treatment of ulcerative colitis (UC). The randomized controlled trials on TCM enema intervention in the treatment of UC were searched in seven databases: PubMed, Embase, Web of Science, CBM, CNKI, Wanfang Database, and VIP Database from January 1, 2013 to June 6, 2022, and the data were analyzed using RevMan 5.3 software. A total of 18 studies involving 1514 UC patients were included. Meta analysis results showed that compared with conventional Western medicine, Chinese medicine enema had a significant effect on UC, and the clinical effective rate of the experimental group using Chinese medicine enema was 4.45 times that of the control group using conventional Western medicine (odds ratio = 4.45, 95% confidence interval [3.27, 6.06]). Therefore, Chinese medicine enema is effective in the treatment of UC, and can significantly reduce related symptoms.